Coating composition, UV light conversion coating and preparation method thereof, photovoltaic cell and photovoltaic module
By using a coating composition of glycidyl ether type epoxy resin, alicyclic epoxy resin and vinyl ether monomer in liquid form at room temperature, the UV light conversion coating is formed, which solves the problem that photovoltaic cells cannot effectively utilize UV wavelengths, and improves the efficiency and service life of the photovoltaic cells.
Patent Information
- Application Number
- CN202411487332.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Existing photovoltaic cells are unable to effectively utilize the entire solar spectrum, especially the shorter UV wavelengths, resulting in reduced efficiency and short service life.
A coating composition, including glycidyl ether type epoxy resin, alicyclic epoxy resin and vinyl ether monomers, is liquid at room temperature, to form a UV light conversion coating by cationic polymerization.
The conversion efficiency of photovoltaic cells to UV light is improved, the transmittance of the UV band is reduced, and the transmittance of visible light wavelength is increased, and the service life of photovoltaic cells is extended.
Smart Images

Figure SMS_1 
Figure SMS_10 
Figure SMS_11
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of photovoltaic cells, and in particular to a coating composition for forming a UV light conversion coating for a photovoltaic cell, a UV light conversion coating prepared using the coating, a method for preparing the UV light conversion coating, and a photovoltaic cell and a photovoltaic module comprising the coating. Background Art
[0002] With the consumption of traditional fossil energy and the deterioration of the ecological environment for human survival, clean renewable energy such as solar energy, wind energy, and hydropower have long been highly valued by the world. Among them, solar energy, with its inexhaustible characteristics and advantages, can be said to be the best choice for mankind to solve the energy shortage problem in the 21st century. The core components of photovoltaic power generation are photovoltaic cells and modules. The goal is to continuously improve the power conversion efficiency of battery modules and reduce the cost of power generation, so as to ultimately achieve "grid parity".
[0003] The spectrum of sunlight ranges from 300nm to 2400nm, and can generally be divided into ultraviolet light, visible light, and infrared light. Ultraviolet light (UV) is a general term for radiation with a frequency of 750THZ-30PHz in the electromagnetic spectrum, corresponding to a wavelength of 380nm-10nm in a vacuum. When sunlight is incident on a photovoltaic cell module, due to the limitation of the photovoltaic cell material itself in responding to the wavelength of light, it can only absorb a portion of light of a specific wavelength, and the shorter UV wavelength cannot be absorbed and converted into electricity, so that the photovoltaic cell cannot effectively utilize the entire spectrum. Based on the structural characteristics of existing cells, such as HJT, TOPCon, and BC cells, short-wavelength ultraviolet light is destructive to the passivation layer of the cell, thereby reducing the efficiency and service life of the cell.
[0004] Recently, a technology developed to improve the efficiency of photovoltaic devices is to use wavelength down-shifting films, also known as wavelength conversion films, light conversion films or light transfer films. The wavelength down-shifting film can absorb photons of shorter wavelengths and re-emit them at more favorable longer wavelengths, which can then be absorbed by the photoconductive layer in the device and converted into electricity. Since the wavelength down-shifting film can convert the wavelength band of the incident light in which the photovoltaic cell responds poorly (low quantum efficiency) into the wavelength band with better response (high quantum efficiency), it mainly changes the ultraviolet light in the sunlight into usable red and blue light, thereby achieving the maximum utilization of sunlight without changing the structure of the photovoltaic cell itself, thereby increasing the unit power generation.
[0005] The light conversion film is usually prepared by mixing a polymer matrix, a light conversion agent and various other additives; and the light conversion efficiency and other properties of the light conversion film are mainly improved by improving the light conversion agent (see, for example, CN103415589A, CN117431022A), or by changing the combination of the polymer matrix, the light conversion agent and various other components for formula design (see, for example, CN114716948A, CN114836136A, CN118165664A).
[0006] Since the performance of the photoconversion layer significantly affects the performance of the photovoltaic cell and photovoltaic module to which it is applied, it is still desired in the art to provide a photoconversion layer with further improved performance including photoconversion efficiency. Summary of the invention
[0007] The present invention is made in view of the above problems existing in the prior art.
[0008] In a first aspect, the present invention provides a coating composition for forming a UV light conversion coating for a photovoltaic cell, comprising, by mass:
[0009] (A) 100 parts of a first epoxy resin that is liquid at room temperature and contains at least two glycidyl ether groups per molecule;
[0010] (B) 33-66 parts of a second epoxy resin that is liquid at room temperature and is an alicyclic epoxy resin having an average of at least two cycloalkylene oxide groups per molecule;
[0011] (C) 33-66 parts of a vinyl ether monomer that is liquid at room temperature;
[0012] (D) 6-16 parts of a cationic initiator;
[0013] (E) 3-15 parts of a UV light conversion agent; and
[0014] (F) 0-200 parts of an inert diluent.
[0015] In a second aspect, the present invention provides a UV light conversion coating obtainable by (cationic) polymerization of a coating composition according to the first aspect of the invention.
[0016] In a third aspect, the present invention provides a method for preparing a UV light conversion coating according to the second aspect of the present invention, which comprises coating a coating composition according to the first aspect of the present invention on a substrate surface, and subjecting the coated coating composition to (cationic) polymerization.
[0017] In a fourth aspect, the present invention provides a photovoltaic cell comprising a UV light conversion coating according to the second aspect of the present invention formed on a surface of the photovoltaic cell.
[0018] In a fifth aspect, the present invention provides a photovoltaic cell module comprising the UV light conversion coating according to the second aspect of the present invention formed on the inner and / or outer surface of the front glass and / or back glass of the photovoltaic cell module.
[0019] The applicant has found that, compared with the conventional method of mixing a polymer matrix with a photoconverter and then coating the resulting mixture to prepare a photoconverter coating or a photoconverter film, a mixture of a glycidyl ether-type epoxy resin containing at least two glycidyl ether groups that is liquid at room temperature and can be polymerized, an alicyclic epoxy resin containing at least two epoxy cycloalkyl groups that is liquid at room temperature and can be polymerized, and a vinyl ether monomer that is liquid at room temperature and can be polymerized, is used to replace the polymer matrix and the photoconverter to prepare a coating composition, and the coating composition is coated and then polymerized. The resulting photoconverter coating can enable the photovoltaic cell or photovoltaic module to which it is applied to more effectively convert UV light into visible light (i.e., reduce the transmittance of UV band light and increase the transmittance of visible light wavelengths), thereby improving the photoconversion efficiency. In terms of converting UV light into visible light and photoconversion efficiency, the UV photoconverter coating of the present invention can still achieve an effect comparable to or even better than that of a conventional photoconverter coating or film even at a lower thickness. Moreover, compared with the coating composition prepared using a (meth)acrylate monomer component that is liquid at room temperature, the prepared light conversion coating or film has better adhesion to photovoltaic cells or modules under long-term use. DETAILED DESCRIPTION
[0020] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application will be described in detail below. It should be noted that the various aspects, features, implementation methods and advantages described in the present application may be compatible and / or may be combined together.
[0021] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art.
[0022] Those skilled in the art will understand that in the present application, unless otherwise specified, a number containing n significant digits after the decimal point actually also covers the result of rounding a number containing more significant digits after the decimal point to n significant digits after the decimal point. For example, 0.16 actually covers all numbers in the range from greater than or equal to 0.155 to less than 0.165; 0.166 actually covers all numbers in the range from greater than or equal to 0.1655 to less than 0.1665, and so on.
[0023] In this application, unless otherwise specified, even if the term "about" is not used to modify a numerical value, the numerical value should be understood to be modified by "about" in consideration of the measurement error; the term "about" includes a deviation of ±5% of the stated numerical value, that is, for a numerical value a, whether or not it is modified by "about", it should be understood to represent a range of a±5%a, that is, 0.95a to 1.05a. For example, the number "1" should be understood to specifically disclose the numerical value 1, and also disclose the range of 0.95-1.05.
[0024] In the present application, when the temperature, pressure and atmosphere involved are not specifically stated, the temperature is room temperature (also called normal temperature, i.e., about 25° C.), the pressure is atmospheric pressure, and the atmosphere is atmospheric (air) atmosphere.
[0025] In the present application, the term "aliphatic" (also called "fatty") includes chain aliphatic and cycloaliphatic (also called cycloaliphatic). Therefore, in the present application, when referring to "aliphatic" compounds, it includes chain aliphatic compounds (i.e. chain aliphatic compounds), cycloaliphatic compounds (i.e. cyclic aliphatic compounds) or mixtures thereof.
[0026] In the present application, the term "glycidyl ether type epoxy resin" refers to an epoxy resin in which epoxy groups are all derived from glycidyl ether groups, which are reaction products obtainable by condensation reaction of polyhydroxy compounds (including polyols and polyphenols) with, for example, epichlorohydrin.
[0027] In the present application, the term "cycloalkylene oxide" refers to a group formed by connecting two adjacent carbon atoms on a cycloalkyl group to an O atom via a single bond, respectively; the term "cycloaliphatic epoxy resin" or "cycloaliphatic epoxy resin containing cycloalkylene oxide" refers to an epoxy resin containing the above-mentioned "cycloalkylene oxide", which is an epoxy resin obtained by oxidizing the olefinic bonds contained in the alicyclic structure.
[0028] In the present application, "cycloaliphatic epoxy resin" refers to an epoxy resin in which the epoxy groups are all derived from "cyclooxyalkyl" groups.
[0029] In the present application, "epoxy equivalent" has a common meaning in the art, which refers to the number of grams when the epoxy resin contains one equivalent of epoxy groups, and the unit is eq / g or mol / g.
[0030] In this application, the terms "UV light conversion coating", "light conversion coating", and "light conversion coating" have the same meaning and are used interchangeably.
[0031] In the present application, the terms "UV light conversion agent", "light conversion agent", "light conversion agent" have the same meaning and are used interchangeably.
[0032] In the present application, the term "alkylene group" refers to a group formed by removing two or more hydrogen atoms from an alkyl group, that is, a divalent or higher alkylene group.
[0033] In the present application, the term "inert" means that it does not react with other components in the composition during the preparation of the composition and does not participate in polymerization during the polymerization process. Therefore, in the present application, the term "inert diluent" means that it does not react with other components in the coating composition during the preparation of the coating composition and does not participate in polymerization during the polymerization and curing process of the coating composition, and is used to dilute the composition, thereby reducing its viscosity, and is a liquid substance at room temperature. Similarly, the term "inert polymer (matrix)" refers to such a polymer: it is added to the coating composition and does not react with other components in the coating composition during the preparation of the coating composition and does not participate in polymerization during the polymerization and curing process of the coating composition.
[0034] In this application, the term "viscosity" refers to dynamic viscosity, the unit of which is cP (i.e. centipoise). The viscosity is measured using a Brookfield viscometer (eg, using a CP40 or CP51 rotor) at 5 rpm.
[0035] In the present application, when describing the amount or number of substances, unless otherwise specified, it refers to mass or mass part.
[0036] The present invention relates to a coating composition for forming a UV light conversion coating for a photovoltaic cell, a UV light conversion coating prepared therefrom, a method for preparing the UV light conversion coating, and a photovoltaic cell and a photovoltaic module comprising the UV light conversion coating.
[0037] The present invention will be described in detail below.
[0038] Coating composition
[0039] In a first aspect, the present invention relates to a coating composition for forming a UV light conversion coating for a photovoltaic cell, comprising, by mass:
[0040] (A) 100 parts of a first epoxy resin that is liquid at room temperature and is a glycidyl ether type epoxy resin having an average of at least two glycidyl ether groups per molecule;
[0041] (B) 33-66 parts by mass of a second epoxy resin that is liquid at room temperature and is an alicyclic epoxy resin having an average of at least two cycloalkylene oxides per molecule;
[0042] (C) 33-66 parts of a vinyl ether monomer that is liquid at room temperature;
[0043] (D) 6-16 parts of a cationic initiator;
[0044] (E) 3-15 parts of a UV light conversion agent; and
[0045] (F) 0-200 parts of an inert diluent.
[0046] The applicant has found that, compared with the conventional method of directly coating a light conversion coating or a light conversion film by using a coating composition prepared by mixing a polymer matrix with a light conversion agent, a coating composition prepared by mixing a glycidyl ether type epoxy resin containing at least two glycidyl ether groups per molecule which is liquid at room temperature, an alicyclic epoxy resin containing at least two epoxy cycloalkyl groups per molecule which is liquid at room temperature, and a mixture of a vinyl ether monomer which is liquid at room temperature and a polymerization initiator which is liquid instead of a polymer matrix with a light conversion agent is used, and the coating composition is then polymerized after coating, and the obtained light conversion coating can make the photovoltaic cell or photovoltaic module to which it is applied more effectively convert UV light into visible light (i.e., reduce the transmittance of UV band light and increase the transmittance of visible light wavelengths) under the same other conditions (including the same thickness), thereby improving the light conversion efficiency. And in terms of converting UV light into visible light and light conversion efficiency, the UV light conversion coating of the present invention can still achieve an effect comparable to or even better than that of a conventional light conversion coating or film even at a lower thickness. This is believed to be because the coating composition of the present invention uses relatively small molecular weight glycidyl ether epoxy resin, alicyclic epoxy resin and vinyl ether monomer, which have better solubility in photoconversion agent than the high molecular weight polymer matrix used in the prior art photoconversion film or coating, and because these components are liquid at room temperature, they can be mixed with the photoconversion agent more easily and more evenly; in addition, because these epoxy resins contain at least two epoxy groups and the vinyl ether monomer may also optionally contain two vinyl groups, they act as crosslinking agents, so that the coating composition forms a crosslinking structure after curing and polymerization, which limits the migration and even precipitation of the photoconversion agent in the system (for example, due to the segment movement of the polymer matrix and the melting of the polymer matrix at high temperature), so that the system remains more uniform and stable, thereby improving the photoconversion performance and life of the photoconversion layer. In addition, the present invention significantly improves the curing rate of the composition by using alicyclic epoxy resin, thereby improving the production efficiency of the photoconversion layer or film. The coating composition of the present invention can be easily prepared into a photoconversion coating simply by irradiating UV light. In addition, compared with a coating composition prepared using a (meth)acrylate monomer component that is liquid at room temperature, the light conversion coating or film prepared from the coating composition of the present invention has better adhesion to photovoltaic cells or modules under long-term use.
[0047] In an embodiment, the coating composition includes a first epoxy resin that is liquid at room temperature, which is an epoxy resin containing at least two glycidyl ether groups per molecule on average. The first epoxy resin may be, for example, a reaction product containing two or more glycidyl ether groups per molecule formed by condensation reaction of one or more polyhydroxy compounds selected from diols, trihydric or higher polyols, dihydric phenols, trihydric or higher polyphenols with epichlorohydrin. The polyhydroxy compound may, for example, be an aliphatic polyhydroxy compound (e.g., a chain aliphatic polyhydroxy compound or a cycloaliphatic polyhydroxy compound), an aromatic polyhydroxy compound, or any combination thereof. The aliphatic polyhydroxy compound may be a polymeric polyhydroxy compound, a non-polymeric polyhydroxy compound, or a mixture thereof. The aliphatic polyhydroxy compound may be, for example, one or more selected from the following: C2-C20 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C19, C20, or a range defined by any two of them) (e.g., aliphatic (including chain aliphatic and cycloaliphatic)), for example, C2-C10 polyols such as diols, triols, tetraols or higher alcohols, or C6-C20 (e.g., C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C19, C20, or a range defined by any two of them) polyphenols such as diphenols, triphenols, tetrahydric or higher phenols, including alkylene glycols such as ethylene glycol, propylene glycol (e.g., 1,2-propylene glycol, 1,3-propylene glycol, or a combination thereof), butanediol (e.g., 1,2-butanediol), diol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, other linear isomer diols or combinations thereof), pentanediol (e.g., 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 2-methyl-1,4-butanediol, other linear isomer diols (e.g., 2,2-dimethyl-1, 3-propylene glycol (i.e. neopentyl glycol) or a combination thereof), hexanediol (e.g. 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol, 2,3-hexanediol, 2,4-hexanediol, 2,5-hexanediol, 3,4-hexanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, other linear isomer diols or a combination thereof), heptanediol (e.g. 1 , 2-heptanediol, 1,3-heptanediol, 1,4-heptanediol, 1,5-heptanediol, 1,6-heptanediol, 1,7-heptanediol, 2,3-heptanediol, 2,4-heptanediol, 2,5-heptanediol, 2,6-heptanediol, 3,4-heptanediol, 3,5-heptanediol, 2-methyl-1,6-hexanediol, 3-methyl-1,6-hexanediol, other linear isomer diols or combinations thereof), octanediol (e.g., 1,2-octanediol, 1,3-octanediol, 1,4-octanediol, 1,5-octanediol, 1,6-octanediol, 1,7-octanediol, 1,8-octanediol, 2-methyl-1,7-heptanediol, 3-methyl-1,7-heptanediol, 4-methyl-1,7-heptanediol, other linear isomer diols or combinations thereof), nonanediols (e.g., 1,2-nonanediol, 1,3-nonanediol, 1,4-nonanediol, 1,5-nonanediol, 1,6-nonanediol, 1,7-nonanediol, 1,8-nonanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 3-methyl-1,8-octanediol , 4-methyl-1,8-octanediol, other linear isomer diols or combinations thereof), decanediol (e.g., 1,2-decanediol, 1,3-decanediol, 1,4-decanediol, 1,5-decanediol, 1,6-decanediol, 1,7-decanediol, 1,8-decanediol, 1,9-decanediol, 1,10-decanediol, 2-methyl-1,9-nonanediol, 3-methyl-1,9-nonanediol, 4-methyl-1,9-nonanediol, 5-methyl-1,9-nonanediol, other linear isomer diols or combinations thereof), cyclohexanediol (e.g., 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1, 4-cyclohexanediol or a combination thereof), cyclohexanedimethanol (e.g., 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol), glycerol, diglycerol, trimethylolpropane, pentaerythritol, dipentaerythritol; ether polyols derived from (e.g., those mentioned above) C2-C20 polyols such as alkylene glycols (e.g., adducts of alkylene glycols and alkylene oxides having a different carbon number from the alkylene glycol (e.g., ethylene oxide, propylene oxide, butylene oxide, etc., or a combination thereof); polyalkylene oxide diols (also called polyether diols) (e.g., adducts of alkylene oxides (e.g., ethylene oxide, propylene oxide, butylene oxide, etc., or a combination thereof) butylene oxide, etc. or a combination thereof) such as diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol (e.g., 200, 300, 400, 600), dipropylene glycol, tripropylene glycol, tetrapropylene glycol, polypropylene glycol (e.g., 200, 300, 400, 600), bisphenol and its hydrogenation product (i.e., hydrogenated bisphenol) such as bisphenol A, hydrogenated bisphenol A, bisphenol F, hydrogenated bisphenol F, bisphenol S, hydrogenated bisphenol S, triphenol or higher phenol and its hydrogenation product; castor oil; but not limited thereto. Preferably, the polyhydroxy compound is a dihydroxy compound, preferably hydrogenated bisphenol A. ,
[0048] In a preferred embodiment, the first epoxy resin has a viscosity of 100-100000 cp, such as 500-10000 cp, such as 1000-5000 cp at 25° C. For example, it may have the following viscosities: 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500, 3600 , 3700, 3800, 3900, 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 4900, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, 65000, 70000, 75000, 80000, 85000, 90000, 95000, 100000 cp, or a range limited by any two of them. As previously described, the viscosity can be measured using a Brookfield viscometer CP51 spindle at 5 rpm.
[0049] The epoxy equivalent of the first epoxy resin is not particularly limited, and can be, for example, 100-2000 g / mol, for example 100-500 g / mol, for example 200-300 g / mol. g / mol, for example 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000 g / mol, or a range defined by both of them.
[0050] In one embodiment, the first epoxy resin is a reaction product formed by condensation reaction of hydrogenated bisphenol A and epichlorohydrin, containing an average of two glycidyl ether groups per molecule, also referred to as hydrogenated bisphenol A diglycidyl ether or hydrogenated bisphenol A diglycidyl ether resin in this application.
[0051] The first epoxy resin can be, for example, a commercially available product, such as hydrogenated bisphenol A diglycidyl ether, such as CYD-128 and CYD-127 of Baling Petrochemical, DER330 and DER331 of Dow Chemical, NPEL127 and NPEL128 of Nan Ya Epoxy Resin (Kunshan) Co., Ltd., XY518 of Anhui Xinyuan Technology Co., Ltd., ADEKA EP4080E, etc.
[0052] In an embodiment, the composition includes 33-66 parts by mass of a second epoxy resin that is liquid at room temperature relative to 100 parts by mass of the first epoxy resin, which is an alicyclic epoxy resin containing at least two epoxy cycloalkyl groups per molecule on average. For example, the composition may include the following amount of the second epoxy resin relative to 100 parts by mass of the first epoxy resin: 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66 parts by mass, or a range defined by any two of them.
[0053] In a preferred embodiment, the second epoxy resin has a viscosity of 10-50000, such as 50-2000, such as 100-500 cp at 25° C. For example, it may have the following viscosities: 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500 00, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500, 3600, 3700, 3800, 3900, 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 4900, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000 cp, or a range limited by any two of them. As previously described, the viscosity can be measured using a Brookfield viscometer CP51 spindle at 5 rpm.
[0054] The epoxy equivalent of the second epoxy resin is not particularly limited, for example, it can be 100-1000 g / mol, for example, 100-500 g / mol, for example, 100-150 g / mol, for example, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 600, 700, 800, 900, 1000 g / mol, or a range defined by both of them.
[0055] In a preferred embodiment, the second epoxy resin can be represented by the following formula I:
[0056]
[0057] Formula I
[0058] Wherein L1 is selected from a single bond or a C1-C30 (e.g., C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C19, C20, C21, C22, C23, C24, C25, C26, C27, C28, C29, C30, or a range defined by any two of them) divalent or higher alkylene (e.g., divalent alkylene) optionally containing one or more groups selected from -O-, C=O, -C(=O)O-, -OC(=O)-, -OC(=O)O-, -Si(CH3)2-;
[0059] a and b are each independently an integer of 0-7, preferably 1-4, and a+b=2-10, preferably 2-5, more preferably a and b are each independently selected from 1 or 2, and further preferably a=1 and b=2.
[0060] For example, the second epoxy resin may be one or more selected from the following:
[0061] (1) Bis((3,4-epoxycyclohexyl)methyl)adipate:
[0062] ;
[0063] (2) 3,4-Epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate:
[0064] ;
[0065] (3) 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylate):
[0066] ;
[0067] (4) Bis(3,4-epoxycyclohexylmethyl)carbonate:
[0068] ;
[0069] (5) (3,4,3',4'-Diepoxy)bicyclohexane:
[0070] ;
[0071] (6) 2,2-Bis(3,3'-epoxycyclohexyl)propane:
[0072] ;
[0073] (7) 6-[[6-[[6-(7-oxabicyclo[4.1.0]heptane-3-methoxy)-6-oxohexyl]oxy]-6-oxohexyl]oxy]-6-oxohexyl 7-oxabicyclo[4.1.0]heptane-3-carboxylate:
[0074] ;
[0075] (8) 1,1,3,3-Tetramethyl-1,3-bis-[2-[7-oxybicyclo[4.1.0]hept-3-yl]ethyl]disiloxane:
[0076] ;
[0077] But it is not limited to this.
[0078] In one embodiment, the second epoxy resin is 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate.
[0079] The applicant has found that when a first epoxy resin (A) and a vinyl ether monomer (C) are added without adding a second epoxy resin (B) which is an alicyclic epoxy resin, the composition cures very slowly or even does not cure when cured by UV light; when a second epoxy resin which is an alicyclic epoxy resin is further added, the curing rate of the composition is significantly improved, and the composition cures smoothly, thereby improving the production efficiency of the light conversion layer or film.
[0080] The second epoxy resin may be, for example, a commercially available product, such as 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexyl carboxylate, which may be, for example, TTA21S, TTA21L, TTA21P, TTA21LP from Jiangsu Taitel Chemical Co., Ltd., 2021P from Daicel Japan, S-21 from Yantai Donghua New Materials Co., Ltd.
[0081] In an embodiment, the composition includes 33-66 parts of a vinyl ether monomer that is liquid at room temperature relative to 100 parts by mass of the first epoxy resin. For example, the coating composition may include 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66 parts by mass of the first epoxy resin, or a range defined by any two of them. The applicant has found that when the amount of vinyl ether monomer in the composition is within the above range of 33-66 parts by mass, on the one hand, compared with a lower amount of vinyl ether monomer, the solubility of the photoconverter can be further increased, so that it is completely dissolved and thus more evenly dispersed, which is conducive to obtaining a photoconversion layer that can more effectively convert UV light into visible light and thus has a higher photoconversion efficiency; on the other hand, compared with a higher amount of vinyl ether monomer, the prepared photoconversion coating has significantly better adhesion to photovoltaic cells or panels, and at the same time, the yellowing index of the photoconversion coating is reduced, its anti-aging property is improved, and a lower UV band transmittance and a higher photoconversion efficiency are achieved.
[0082] In a preferred embodiment, the vinyl ether monomer can be represented by the following formula II:
[0083] CH2=CHOROR1
[0084] Formula II
[0085] Wherein, R is selected from one or more of the following:
[0086] C2-C10 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, or a range defined by any two of them), such as C2-C6 alkylene such as (CH2)n, n=2-6; and
[0087] Residues derived from diethylene glycol, triethylene glycol, polyethylene glycol (e.g., 200, 300, 400, 600), dipropylene glycol, tripropylene glycol, or polypropylene glycol (e.g., 200, 300, 400, 600);
[0088] and
[0089] R1=H or -CH=CH2.
[0090] In other words, the vinyl ether monomers may contain an average of 1 or 2 vinyl groups per molecule. The vinyl ether monomers may be all monovinyl terminated monomers (one or more), or all divinyl terminated monomers (one or more), or a mixture of monovinyl terminated monomers (one or more) and divinyl terminated monomers (one or more).
[0091] In one embodiment, the vinyl ether monomer is diethylene glycol monovinyl ether, triethylene glycol divinyl ether, or a combination thereof.
[0092] In an embodiment, the composition includes a cationic initiator. The cationic initiator is an initiator capable of initiating polymerization of both epoxy and vinyl. The cationic initiator can be appropriately selected according to the intended application and can be, for example, a cationic photoinitiator, a cationic thermal initiator, or a combination thereof, preferably a cationic photoinitiator. The cationic photoinitiator can, for example, include or be selected from one or more of iodonium salts (e.g., diaryl iodonium salts), sulfonium salts (sulfonium salts) (e.g., triaryl sulfonium salts, alkyl sulfonium salts), iron arene salts, sulfonyloxy ketones, and triaryl siloxanes. The cationic photoinitiator can, for example, be one or more of the following compounds 1-5. The cationic photoinitiator can be a commercially available product, such as TR-PAG-30301P (Compound 1), TR-PAG-30201P (Compound 2), TR-PAG-20102P (Compound 3), TR-PAG-202 (Compound 4), and TR-PAG-201S (Compound 5) of Changzhou Qiangli Electronic New Materials Co., Ltd.
[0093]
[0094] Compound 1: TR-PAG-30301P
[0095]
[0096] Compound 2: TR-PAG-30201P
[0097]
[0098] Compound 3: TR-PAG-20102P
[0099]
[0100] Compound 4: TR-PAG-202
[0101]
[0102] Compound 5: TR-PAG-201S
[0103] The amount of the initiator is not particularly limited, and is present in the coating composition in an amount that is effective to initiate polymerization of the system (polymerization of both epoxy groups and vinyl groups). In an embodiment, the coating composition may include the following amount of initiator relative to 100 parts by mass of the first epoxy resin: 6-16 parts by mass, for example 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 parts by mass, or a range defined by any two of them.
[0104] In an embodiment, the composition includes a UV light conversion agent. In the present application, the UV light conversion agent is also referred to as a light conversion agent or a light conversion agent. The UV light conversion agent is not particularly limited and may be various UV light conversion agents commonly used in the art. Preferably, the UV light conversion agent is a UV light conversion agent that does not adversely affect polymerization during the polymerization of the composition. The UV light conversion agent may, for example, include one or more selected from organic fluorescent materials, rare earth luminescent materials, and quantum dot luminescent materials. The organic fluorescent material may include benzotriazole fluorescent materials (such as the light converter E1 shown below), rhodamine fluorescent materials (such as rhodamine B (light converter E2) with the structure shown below), carbocyclic materials (such as fluorescent brightener ER, fluorescent brightener CBS-X, etc.), triazine amino diphenylethylene materials (such as fluorescent brightener DMS), organic triazoles, diphenylethylene-triazole materials (such as Tinopal PBS, Blankophor BHC, etc.), benzoxazole materials (such as fluorescent brightener OB-1, fluorescent brightener 393, etc.), furan, benzofuran, benzimidazoles, benzotriazoles and benzothiadiazole skeletons.
[0105]
[0106] The applicant has found that when a benzotriazole fluorescent material is used in the coating composition of the present invention, the prepared light conversion coating can achieve slightly better light conversion efficiency than when other light conversion agents such as rhodamine fluorescent materials are used.
[0107] In an embodiment, the coating composition includes 3-5 parts by mass of the photoconverter relative to 100 parts by mass of the first epoxy resin, for example, 3.0, 3.5, 4.0, 4.5, 5.0 parts by mass, or a range defined by any two of them.
[0108] In an embodiment, the coating composition may further optionally include an inert diluent, depending on the desired viscosity. The diluent is not particularly limited and may, for example, include or be one or more of ethyl acetate, butyl acetate, dimethyl carbonate, acetone, butanone, cyclohexanone, propylene carbonate, etc.
[0109] The amount of the diluent is not particularly limited. For example, the coating composition may include the following amount of diluent relative to 100 parts by mass of the first epoxy resin: 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 parts by mass, or a range limited by any two of them.
[0110] The coating composition may not contain an inert (i.e., non-reactive, e.g., non-polymerizable) polymer matrix commonly used in the art; the coating composition forms a crosslinked polymer by polymerization of the first epoxy resin, the second epoxy resin, and the vinyl ether monomer contained therein. However, the coating composition may also contain an inert polymer matrix commonly used in the art without departing from the spirit and scope of the present invention. For example, the coating composition may contain one or more of the following inert polymer matrices: polyethylene terephthalate, polymethyl methacrylate, polyvinyl butyral, ethylene vinyl acetate copolymer, ethylene tetrafluoroethylene copolymer, polyimide, amorphous polycarbonate, polystyrene, polyurethane, polyacrylate, and combinations thereof. The amount of the polymer matrix is not particularly limited and can be an appropriate amount that can be dissolved in the coating composition of the present invention, for example, it can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 parts by mass, or a range limited by any two thereof.
[0111] The coating composition may also optionally include one or more other auxiliary agents (or additives) commonly used in the light conversion layer in the art. The auxiliary agent may include, for example, one or more of the following: light stabilizer, antioxidant, etc. The light stabilizer is any one of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer, and a hydroperoxide decomposer light stabilizer, or a mixture of at least two thereof; the antioxidant is any one of a hindered phenol antioxidant, an aromatic amine antioxidant, a phosphite antioxidant, a thioether antioxidant, and a metal passivator antioxidant, or a mixture of at least two thereof.
[0112] The amount of the auxiliary agent used may be a commonly used amount in the art. For example, in the coating composition, the amount of each auxiliary agent may be 0.1-5 parts by mass.
[0113] UV light conversion coating
[0114] In a second aspect, the present invention relates to a UV light converting coating obtained by (cationic) polymerization of a coating composition according to the first aspect of the invention.
[0115] The (cationic) polymerization can be carried out by methods known in the art, depending on the type and amount of cationic initiator included in the coating composition. For example, when a cationic thermal initiator is included, the coating composition can be polymerized at a temperature that allows the thermal initiator to decompose and form cations; when a photoinitiator is included, the coating composition can be polymerized by exposing it to radiation, such as UV light. When both a thermal initiator and a photoinitiator are included, thermally initiated polymerization can be carried out first, followed by photoinitiated polymerization, or photoinitiated polymerization can be carried out first, followed by thermally initiated polymerization, or both thermally initiated and photoinitiated polymerization can be carried out simultaneously. The conditions and details of the cationic polymerization are well known in the art and are not described in detail herein.
[0116] The thickness of the light conversion coating is not particularly limited, and can be a thickness commonly used for light conversion coatings in the art taking into account factors such as light conversion efficiency and durability of the light conversion coating. For example, the thickness of the light conversion coating can be 0.5 μm-1 mm, such as 0.5, 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900, 1000 μm, or a range defined by any two thereof.
[0117] By using the coating composition according to the first aspect of the present invention, the thickness, shape and size of the required UV light conversion coating can be flexibly controlled as needed; and in terms of converting UV light into visible light (i.e., reducing the transmittance of UV band light and increasing the transmittance of visible light wavelengths) and conversion efficiency, the UV light conversion coating of the present invention can still have an effect comparable to or even better than that of commercially available thicker (e.g., 100 μm) commercial light conversion films even at a very thin thickness, such as less than 100 μm, such as less than 80 μm, or even less than 50 μm.
[0118] Preparation method of UV light conversion coating
[0119] In a third aspect, the present invention relates to a method for preparing a UV light conversion coating according to the second aspect of the invention, which comprises coating a coating composition according to the first aspect of the invention on a substrate surface, and subjecting the coated coating composition to (cationic) polymerization, for example by irradiating UV light.
[0120] The substrate may be, for example, a photovoltaic cell or a photovoltaic module.
[0121] The coating can be carried out by any suitable means known in the art. For example, the coating can be carried out by spraying, brushing, knife coating, casting, roller coating, etc.
[0122] The (cationic) polymerization can be carried out by methods known in the art, depending on the type and amount of cationic initiator included in the coating composition. For example, when a cationic thermal initiator is included, the coating composition can be polymerized at a temperature that allows the thermal initiator to decompose and form cations; when a photoinitiator is included, the coating composition can be polymerized by exposing it to radiation, such as UV light. When both a thermal initiator and a photoinitiator are included, thermally initiated polymerization can be carried out first, followed by photoinitiated polymerization, or photoinitiated polymerization can be carried out first, followed by thermally initiated polymerization, or both thermally initiated and photoinitiated polymerization can be carried out simultaneously. The conditions and details of the cationic polymerization are well known in the art and are not described in detail herein.
[0123] In addition, when the coating composition includes an inert diluent, the inert diluent may be removed after coating, before, during and / or after polymerization. The removal may be performed by conventional means in the art, such as air-drying or drying.
[0124] Photovoltaic cells
[0125] In a fourth aspect, the present invention relates to a photovoltaic cell comprising a UV light conversion coating according to the second aspect of the present invention formed on a surface of the photovoltaic cell.
[0126] The structure of a photovoltaic cell is well known in the art and will not be described in detail here.
[0127] The UV light conversion coating may be formed on a photovoltaic cell by directly coating the coating composition according to the first aspect of the invention on the surface of the photovoltaic cell, followed by (cationic) polymerization, for example by irradiation with UV light.
[0128] Alternatively, the UV light conversion coating can also be formed on the photovoltaic cell by directly coating the coating composition according to the first aspect of the present invention on the surface of other substrates, followed by (cationic) polymerization, for example, by irradiating UV light; and then peeling the obtained film from the carrier and then setting it on the surface of the photovoltaic cell.
[0129] The arrangement can be performed by directly laminating the film on the photovoltaic cell surface. Alternatively, the arrangement can also be performed by treating the photovoltaic cell surface (eg, corona treatment, application of adhesive, etc.) and then laminating the film on the treated photovoltaic cell surface.
[0130] After being applied on the surface of the photovoltaic cell, no other functional layer may be further applied on the exposed surface of the photoconversion coating. Alternatively, a protective layer, for example, for further inhibiting the penetration of oxygen and moisture into the photoconversion coating, may also be further applied on the exposed surface of the photoconversion coating. The protective layer may include a polymer matrix. In some embodiments, the polymer matrix of the protective layer may include a substance selected from the following: polyethylene terephthalate, polymethyl methacrylate, polyvinyl butyral, ethylene vinyl acetate copolymer, ethylene tetrafluoroethylene copolymer, polyimide, amorphous polycarbonate, polystyrene, siloxane sol-gel, polyurethane, polyacrylate and combinations thereof. The thickness of the protective layer is not particularly limited, and may, for example, range from about 10 μm to about 2 mm, for example, from about 20 μm to about 1 mm.
[0131] By using the UV light conversion coating of the second aspect of the present invention, the resulting photovoltaic cell can more effectively convert UV light into visible light (i.e., reduce the transmittance of UV band light and increase the transmittance of visible light wavelengths) compared to using conventional light conversion films, thereby improving the light conversion efficiency.
[0132] Photovoltaic cell modules
[0133] In a fifth aspect, the present invention relates to a photovoltaic cell module comprising a UV light conversion coating according to the second aspect of the present invention formed on the inner and / or outer surface of the front glass and / or back glass of the photovoltaic cell module.
[0134] Photovoltaic cell assembly, also known as solar cell panel, is a power generation device composed of multiple solar cells connected in series or in parallel and packaged. It usually includes components such as battery cells, packaging materials, backplane, connectors and cables. The structure and composition of photovoltaic cell assembly are well known in the art and will not be described here.
[0135] The above description of the photovoltaic cell according to the fourth aspect of the present invention is also applicable to the photovoltaic cell assembly.
[0136] Example
[0137] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0138] The information of raw materials used in the examples is as follows.
[0139] A1: Epoxy resin XY518 (hydrogenated bisphenol A diglycidyl ether) from Anhui Xinyuan Technology Co., Ltd., viscosity measured by Brookfield viscometer CP51 rotor at 5rpm is 1000-3500cP@25℃, epoxy equivalent weight is 208-233 g / mol
[0140] A2: Epoxy resin EP4080E (hydrogenated bisphenol A diglycidyl ether) from ADEKA, viscosity 2000-2500 cP@25°C measured with Brookfield viscometer CP51 spindle at 5 rpm, epoxy equivalent weight 210-230 g / mol
[0141] B1: Epoxy resin TTA21P (3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexyl carboxylate) from Jiangsu Taitel Chemical Co., Ltd., viscosity 220-450 cP@25°C measured by Brookfield viscometer CP51 spindle at 5 rpm, epoxy equivalent weight 126-135 g / mol
[0142] B2: Epoxy resin S-21 (3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexyl carboxylate) from Yantai Donghua New Materials Co., Ltd., viscosity 220-300 cP @ 25 °C measured by Brookfield viscometer CP51 rotor at 5 rpm, epoxy equivalent weight 126-132 g / mol
[0143] C1: Diethylene glycol monovinyl ether from MacLean Reagents
[0144] C2: triethylene glycol divinyl ether from MacLean Reagents
[0145] D: Cationic initiator TR-PAG-201S from Changzhou Qiangli Electronic New Materials Co., Ltd.
[0146] E1: A light conversion agent from Ruiers Technology Co., Ltd., which is an anti-aging modified benzotriazole fluorescent material with the structure shown above.
[0147] E2: A photoconverter purchased from MacLean Reagent Company, which is a rhodamine fluorescent agent Rhodamine B with the structure shown above
[0148] Test Method
[0149] 1. Light transmittance: According to the standard GB / T 29848-2018, the test was carried out using a UV-visible spectrophotometer (PerkinElmer LAMBDA 950).
[0150] 2. Photoelectric conversion efficiency: The absolute quantum efficiency test was performed using a Horiba spectrometer FL-3 and an integrating sphere at room temperature. Photoelectric conversion efficiency = number of blue light photons emitted / number of ultraviolet light photons absorbed (350nm wavelength excitation).
[0151] 3. Solubility of photoconverter: Using the photoconverter as the solute and a mixed liquid prepared by mixing the above components A1 or A2, B1 or B2, C1 or C2, and D in proportion as the solvent, observe the dissolution of 5 g of the photoconverter E1 or E2 in 100 g of the above mixed liquid.
[0152] 4. Adhesion: The adhesion test is carried out according to the method and conditions specified in ISO 2409; a coating with a thickness of 100μm is scraped on a white glass with a size of 5cm*10cm, and then 10*10 square grids (each grid has a side length of 1mm) are scratched on the coating using a standard knife. After the test, if there is no coating shedding in all 100 grids, it is 5B; if the coating shedding area of 100 grids is not more than 5%, it is 4B; if the coating shedding area of 100 grids is more than 5% but not more than 15%, it is 3B.
[0153] 5. Volume resistivity: The volume surface resistivity tester model BEST-380 produced by Beijing Beiguang Precision Instrument Co., Ltd. is used for testing in accordance with the method specified in GB / T 1410.
[0154] 6. Aging yellowing test: After UV curing, the photoconversion coating film with a thickness of about 100μm was placed in a 200℃ oven. After 3 hours, the film was taken out and the b* value after aging was measured using a spectrophotometer (manufacturer: Hangzhou Caipu Technology Co., Ltd., model CS-821N). This value reflects the photoconversion coating's resistance to aging and yellowing.
[0155] 7. Curing ability: After the coating with a thickness of 100 μm was scraped onto a 5 cm*10 cm white glass, the UVLED curing box model F-UVSF81T of Futanxi (Shanghai) Electronic Technology Co., Ltd. was placed in the above UVLED curing box and the coating was dried under the conditions of 365 nm UV LED and 3000 mJ / cm 2 After curing under the conditions of , check whether the coating is dry and cured by observation and finger touch.
[0156] The above tests were all carried out at 25°C and 50%RH.
[0157] Examples 1-11 and Comparative Examples 1-10
[0158] According to the composition shown in Table 1, vinyl ether monomer C1 or C2, photoconverter E1 or E2 and cationic initiator D are placed in a stirring kettle and stirred until completely dissolved; then epoxy resin A1 or A2 and epoxy resin B1 or B2 are added and stirred and mixed until uniform, thereby preparing the coating compositions of Examples 1-11 and Comparative Examples 1-10, respectively.
[0159] The coating compositions of Examples 1-11 and Comparative Examples 1-10 were respectively scraped onto white glass using a scraper, and then a 365 nm UV LED, 3000 mJ / cm 2 Unless otherwise specified, the thickness of the UV light conversion coating prepared in each example and comparative example is about 100 μm.
[0160] Each embodiment and comparative example was tested by the method described in the test method section, and the test results are shown in Tables 2 and 3. The comparative film shown in Table 2 is a commercially available light conversion film (brand: Saiwu, model: WT11).
[0161] It can be seen from Table 2-3 that, compared with the commercially available light conversion film, the UV light conversion coatings of the same thickness prepared in Examples 1-11 of the present invention significantly reduce the transmittance in the UV band (280-380nm), and increase the transmittance in the visible light band (380-1100nm), thereby improving the light conversion efficiency. In addition, it can also be seen from Table 2 that, even with a lower thickness, the UV light conversion coating of the present invention can achieve a lower transmittance in the UV band (280-380nm), a higher transmittance in the visible light band (380-1100nm), and a higher light conversion efficiency.
[0162] It can also be seen from Table 3 that the coating compositions of Comparative Examples 5 and 6 without adding epoxy resin B1 or B2 were not cured under the above curing conditions, indicating that the addition of epoxy resin B1 or B2 is helpful for the curing of the system.
[0163] In addition, it can be seen from Table 3 that, compared with the light conversion coatings of comparative examples 1-4 using a lower amount of component C1, the light conversion agent in the light conversion coatings of embodiments 1-6 of the present invention using a higher amount of component C1 and other conditions being the same has better solubility, and compared with the light conversion coatings of comparative examples 7-10 using a higher amount of component C1, the light conversion coatings of embodiments 1-6 of the present invention using a lower amount of component C1 and other conditions being the same have significantly better adhesion and a lower yellowing index, indicating that they have higher anti-aging properties. In addition, compared with the light conversion coatings of comparative examples 7 and 9 using a higher amount of component C1 and other conditions being the same, embodiments 2, 4 and 6 using light conversion agent E2 have lower UV band transmittance and higher light conversion efficiency, respectively. Moreover, Examples 1, 3 and 5 using the light conversion agent E1 achieve higher light conversion efficiency than Examples 2, 4 and 6 which differ only in using the light conversion agent E2, indicating that in the system of the present invention, the benzotriazole-based fluorescent material can cause the prepared light conversion coating to achieve slightly better light conversion efficiency than the rhodamine-based fluorescent material.
[0164] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, without departing from the inventive concept of the present invention, improvements can be made to the present invention, but these all belong to the protection scope of the present invention.
[0165] Table 1 Composition of the light conversion coating formulations of various embodiments and comparative examples
[0166]
[0167] Table 2 Comparison of light conversion performance between light conversion coating and light conversion film
[0168]
[0169] Table 3 Light conversion coating performance
[0170]
Claims
1. A coating composition for forming a UV light conversion coating for a photovoltaic cell, comprising, by mass: (A) 100 parts of a first epoxy resin that is liquid at room temperature and contains at least two glycidyl ether groups per molecule; (B) 33-66 parts of a second epoxy resin that is liquid at room temperature, which is an alicyclic epoxy resin containing at least two cycloalkylene oxides per molecule on average, wherein the cycloalkylene oxide refers to a group formed by connecting two adjacent carbon atoms on a cycloalkyl group to an O atom via a single bond; (C) 33-66 parts of a vinyl ether monomer that is liquid at room temperature; (D) 6-16 parts of a cationic initiator; (E) 3-15 parts of a UV light conversion agent; and (F) 0-200 parts of an inert diluent.
2. The coating composition for forming a UV light conversion coating for a photovoltaic cell as claimed in claim 1, wherein the first epoxy resin is a reaction product formed by a condensation reaction of one or more polyhydroxy compounds selected from diols, trihydric or higher polyols, dihydric phenols, trihydric or higher polyphenols with epichlorohydrin, and containing an average of more than two glycidyl ether groups in each molecule.
3. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 2, wherein the polyhydroxy compound is one or more selected from C2-C20 polyols or C6-C20 polyphenols.
4. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 2, wherein the polyhydroxy compound is one or more selected from the following: ethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, decanediol, cyclohexanediol, cyclohexanedimethanol, glycerol, diglycerol, trimethylolpropane, pentaerythritol, dipentaerythritol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 600, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, polypropylene glycol 200, polypropylene glycol 300, polypropylene glycol 400, or polypropylene glycol 600, bisphenol A, hydrogenated bisphenol A, bisphenol F, hydrogenated bisphenol F, bisphenol S, hydrogenated bisphenol S.
5. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 2, wherein the polyhydroxy compound is hydrogenated bisphenol A. 6 . The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1 , wherein the first epoxy resin has a viscosity of 100-100000 cp at 25° C.
7. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the first epoxy resin has a viscosity of 500-10000 cp at 25°C.
8. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the first epoxy resin has a viscosity of 1000-5000 cp at 25°C.
9. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the epoxy equivalent of the first epoxy resin is 100-2000 g / mol.
10. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the epoxy equivalent of the first epoxy resin is 100-500 g / mol.
11. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the epoxy equivalent of the first epoxy resin is 200-300 g / mol.
12. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the second epoxy resin has a viscosity of 10-50000 cp at 25°C.
13. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the second epoxy resin has a viscosity of 50-2000 cp at 25°C.
14. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the second epoxy resin has a viscosity of 100-500 cp at 25°C.
15. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the epoxy equivalent of the second epoxy resin is 100-1000 g / mol.
16. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the epoxy equivalent of the second epoxy resin is 100-500 g / mol.
17. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the epoxy equivalent of the second epoxy resin is 100-150 g / mol.
18. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the second epoxy resin is represented by the following formula I: Formula I wherein L1 is selected from a single bond or a C1-C30 divalent or higher alkylene group optionally containing one or more groups selected from -O-, C=O, -C(=O)O-, -OC(=O)-, -OC(=O)O-, -Si(CH3)2-; and a and b are each independently an integer of 0-7, and a+b=2-10.
19. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 18, wherein a and b are each independently an integer of 1-4.
20. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 18, wherein a+b=2-5.
21. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 18, wherein a and b are each independently selected from 1 or 2.
22. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 18, wherein a=1 and b=2.
23. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the second epoxy resin is one or more selected from the following: (1) Bis((3,4-epoxycyclohexyl)methyl)adipate: ; (2) 3,4-Epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate: ; (3) 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylate): ; (4) Bis(3,4-epoxycyclohexylmethyl)carbonate: ; (5) (3,4,3',4'-Diepoxy)bicyclohexane: ; (6) 2,2-Bis(3,3'-epoxycyclohexyl)propane: ; (7) 6-[[6-[[6-(7-oxabicyclo[4.1.0]heptane-3-methoxy)-6-oxohexyl]oxy]-6-oxohexyl]oxy]-6-oxohexyl 7-oxabicyclo[4.1.0]heptane-3-carboxylate: ; (8) 1,1,3,3-Tetramethyl-1,3-bis-[2-[7-oxybicyclo[4.1.0]hept-3-yl]ethyl]disiloxane: 。 24. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the vinyl ether monomer is represented by the following formula II: CH2=CHOROR1 Formula II in, R is selected from one or more of the following: C2-C10 alkylene; and a residue derived from diethylene glycol, triethylene glycol, polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, polyethylene glycol 600, dipropylene glycol, tripropylene glycol, polypropylene glycol 200, polypropylene glycol 300, polypropylene glycol 400, or polypropylene glycol 600; and R1=H or -CH=CH2.
25. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 24, wherein the C2-C10 alkylene group is a C2-C6 alkylene group.
26. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 24, wherein the C2-C10 alkylene group is (CH2)n, wherein n=2-6.
27. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the vinyl ether monomer is one or more selected from diethylene glycol monovinyl ether and triethylene glycol divinyl ether.
28. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the cationic initiator is a cationic photoinitiator, a cationic thermal initiator or a combination thereof.
29. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the cationic initiator is one or more cationic photoinitiators selected from iodonium salts, sulfonium salts, iron arene salts, sulfonyloxy ketones and triaryl siloxane ethers.
30. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the cationic initiator is one or more selected from the following compounds 1-5: Compound 1 Compound 2 Compound 3 Compound 4 Compound 5.
31. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the UV light conversion agent comprises one or more selected from the group consisting of an organic fluorescent material, a rare earth luminescent material, and a quantum dot luminescent material.
32. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the UV light conversion agent is one or more selected from the following: a benzotriazole fluorescent material and a rhodamine fluorescent material.
33. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, wherein the UV light conversion agent is a benzotriazole fluorescent material.
34. The coating composition for forming a UV light conversion coating for a photovoltaic cell according to claim 1, further comprising 1 to 50 parts by mass of an inert polymer.
35. A UV light conversion coating obtained by polymerizing the coating composition for forming a UV light conversion coating for a photovoltaic cell according to any one of claims 1 to 34.
36. A method for preparing a UV light conversion coating, comprising coating the coating composition for forming a UV light conversion coating for a photovoltaic cell according to any one of claims 1 to 34 on a substrate surface, and polymerizing the coated coating composition.
37. A photovoltaic cell comprising the UV light conversion coating of claim 35 formed on a surface thereof.
38. A photovoltaic cell assembly comprising the UV light conversion coating according to claim 35 formed on the inner surface and / or outer surface of the front glass and / or the back glass of the photovoltaic cell assembly.
Citation Information
Patent Citations
Wavelength conversion film having pressure sensitive adhesive layer to enhance solar harvesting efficiency
CN103415589A
UV light conversion packaging material and preparation method and application thereof
CN114716948A
UV light conversion packaging adhesive film and preparation method thereof
CN114836136A
Light conversion adhesive film composition, light conversion adhesive film and photovoltaic module
CN117431022A
High-weather-resistance solar cell power improvement packaging adhesive film, preparation method thereof and solar cell
CN118165664A
Cited By
Ultraviolet attenuation resistant TOPCon battery and preparation method thereof
CN120826076A